Effect of Finishing Protocols on the Surface Roughness and Fatigue Strength of a High-Translucent Zirconia - Barreto, Larissa Araújo Lopes [UNESP]; Grangeiro, Manassés Tercio Vieira [UNESP]; Prado, Pedro Henrique Condé Oliveira [UNESP]; Bottino, Marco Antonio [UNESP]; Dal Piva, Amanda Maria De Oliveira; Ramos, Nathalia De Carvalho [UNESP]; Tribst, João Paulo Mendes; Junior, Lafayette Nogueira [UNESP] (Hindawi, 2023)
Purpose. In case of need for esthetical improvement of zirconia restorations, an individualization using extrinsic staining can be applied. This study aimed to evaluate the surface roughness and fatigue strength (survival) of high-translucency zirconia (3Y-TZP, YZ®HT, Vita Zanhfabrik) with extrinsic characterization and/or glaze. Methods. Sixty (60) zirconia discs (12 × 1.2 mm) were obtained, sintered, and randomly distributed among three groups (n = 20) according to the surface finishing protocol: C (control), C + G (extrinsic characterization followed by a glaze layer), and G (glaze layer). The surface roughness (Ra) was analyzed with a contact profilometer. Subsequently, the specimens were subjected to a fatigue load profile starting at 120 N during 20,000 cycles at 4 Hz frequency, with a 5% increase at each step until failure. The failed specimens were evaluated under a stereomicroscope. Surface roughness analysis was evaluated by using one-way ANOVA and post hoc Tukey tests (95%); while fatigue survival probability was analyzed with Kaplan-Meier and Mantel-Cox (log- rank, 95%). Results. One-way ANOVA revealed that surface roughness was affected by the finishing protocol, where C + G showed the highest mean value (0.46 ± 0.18 μm)A followed by G (0.30 ± 0.10 μm)B, and C (0.19 ± 0.02 μm)C. While for fatigue strength, the G protocol presented a higher mean value (243.00, and 222.36-263.63)A, followed by C + G (192.75 and 186.61-198.88)B and C (172.50 and 159.43-185.56)C. Conclusion. Surface finishing protocols modify the surface roughness and fatigue strength of high-translucent zirconia. Regardless of the surface roughness, both glazing protocols improved the ceramic fatigue strength, favoring the restoration's long-term survival.